Anti-Fungal Properties of Plant Extracts in vitro against Alternaria solani, the Cause of Early Blight in Potato - Rana, Birendra Bahadur; Wagle, Sampada; Singh, Ashmita Kumari; Sherpa, Yankee; Suwal, Abisha; Khatri, Seema; Subedi, Giridhari (Journal of the Plant Protection Society, 2023)
Early blight, caused by Alternaria solani is one of the destructive diseases of potato. An in vitro experiment was conducted using the poisoned food technique to evaluate the efficacy of acetone extracts of six plant species on the mycelial growth of A. solani. Plant extracts of Artemisia vulgaris, Melia azedarach, Parthenium hysterophorus, Datura stramonium, and Justicia adhatoda at concentrations of 0.1%, 0.5% and 5% prepared from Soxhlet extraction were mixed well in the molten potato dextrose agar (PDA) media and poured into petri plates (90 mm Ø). PDA media treated with a fungicide mancozeb was positive control while the untreated media was negative control. The poisoned plates were inoculated with a 4 mm diameter agar plug of seven days old actively growing A. solani and incubated at 26 ± 2 °C, The radial mycelial growth was recorded after 3rd, 5th, 7th and 9th days of incubation and percentage inhibition growth was calculated by comparing it with negative control plates. Artemisia vulgaris significantly inhibited colonial growth at 0.1% and 0.5% concentrations by 36.07% and 12.48%, respectively, at 5th day of inoculation (dai) as compared to negative control. M. azedarach (0.72%), P. hysterophorus (10.17%) and D. stramonium (10.20%) were moderately inhibitory in effect at 1% concentration while J. adhatoda did not possess inhibitory effect on the mycelial growth of A. solani at 5th dai. All the tested extracts were found with some antifungal activity at 5% concentration. A. vulgaris can be exploited as a potent alternative to fungicides for controlling A. solani.